TEACHING SCIENCES AND BIOLOGY FOR DEAF INDIVIDUALS: INVESTIGATING THE CONTEXT OF TEACHING PRACTICE IN REGULAR CLASSROOMS OF A MUNICIPALITY IN THE STATE OF PARANÁ - Lucken Bueno Lucas; Renan Guilherme Pimentel; Simone Luccas (Universidade Federal de Sergipe, 2018)
The process of school inclusion for people with disabilities is a recent development, especially for the deaf individuals, so the study of how this inclusion process occurs and the teaching of Sciences/Biology for these individuals is still incipient. The objective of this work was to investigate how science/biology teaching takes place for deaf students in the city of Cornélio Procópio-PR and what difficulties are encountered by the students, teachers, and sign language interpreters in the scenario of school inclusion. To reach this goal, we interviewed teachers and interpreters who work in elementary and middle schools of the public network that attend deaf students in Cornélio Procópio. The results of the interviews demonstrated that all those involved in this process face difficulties, the interpreters indicate language as an obstacle to the interpretation of Sciences and Biology classes, since Brazilian Sign Language presents a deficit of lexicons in relation to the Portuguese Language. On the other hand, the main difficulty for the teachers is the lack of preparation to work in classes which include deaf people, jeopardizing not only their interaction with the students, but also the teaching of Sciences and Biology.